Sex, desire and masturbation : An interpretative phenomenological analysis of sexual health education for young women - Hanson, Jodie (Manchester Metropolitan University, 2014)
British, Sex and Relationship Education has been condemned by Ofsted as ‘not yet good enough’ (2013:6). Previous literature would suggest this is through the absence of desire based knowledge. Other research would highlight the issue of masturbation as a construct to the improvement of the sexual health. However, as genital masturbation is often a taboo within feminine culture the current study used Interpretative Phenomenological Analysis (Smith, 1996, 1999) to assess the intrinsic values of six young women regarding their sexual health and desires. Participants ranged in sexual knowledge from undergone several years of sexual health education to limited sexual health education; forming the basis for the current national education system. Analysis of the data revealed three master themes: pleasure conflict, ‘That Girl’ complex and sexual discourse. A working model of sexual health needs was then proposed in order to address the hierarchy of erotic plasticity the participants showed. Ramifications of socio-political implications towards feminine desire and masturbation are detrimental to sexual health improvement.
https://e-space.mmu.ac.uk/576583/1/Jodie%20Hanson.pdf
Keywords: 2000 à aujourd'hui; 2010-2019; angleterre; discipline; europe; jeunes femmes*; masturbation féminine; mémoires/thèses; périodes historiques; ressource en ligne; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; sexualité des femmes*; thématiques; éducation sexuelle; études qualitatives

La régulation sociale des minorités sexuelles: l'inquiétude dela différence - Corriveau, Patrice; Daoust, Valérie; ProQuest (Firme) (Les Presses de l'Université du Québec, 2011)
Successivement condamnées par la religion, criminalisées par le droit pénal et finalement médicalisées, les minorités sexuelles ont subi une forte répression institutionnelle. Depuis, les luttes des mouvements gais et lesbiens ont conduit, dans certains pays, à la reconnaissance des droits des homosexuels au mariage et à la parentalité. Toutefois, l’homosexualité est encore trop souvent perçue comme une menace à la tradition et à l’ordre « naturel ». Réunissant les contributions de chercheurs en sociologie, en philosophie, en criminologie, en histoire, en anthropologie, en sexologie et en travail social, cet ouvrage porte sur les multiples modes de régulation institutionnelle et sociale des minorités sexuelles. Tout en exposant les différentes pratiques de répression employées par le passé, les auteurs traitent de sujets contemporains comme l’homophobie dans les écoles et l’homoparentalité. Soulevant des questions de justice sociale, ils rappellent que tous, gais et lesbiennes y compris, sont engagés dans le processus de régulation des minorités sexuelles.
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; belgique; canada; cours; criminologie; discipline; europe; histoire; homophobie; hétérosexisme; justice sociale; militance; philosophie; premier cycle; queer; québec; régions géographiques; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; travail social; études gaies et lesbiennes

Young men, masculinities and sex education - Limmer, Mark (Sex Education : Sexuality, Society and Learning, 2010)
This paper draws on focus group and interview data from 45 young men from the north of England to explore the barriers to effective sex and relationships education (SRE). Recent policy debates in relation to establishing statutory SRE in schools provide an opportunity to revisit how it is currently delivered to, and received by, young men. The paper considers the central role played by masculinities and how this role is mediated by social exclusion and poor engagement; it is suggested that addressing masculinities directly should be a priority for future SRE. In conclusion, some tentative approaches to addressing the issues are suggested.
Keywords: 2000 à aujourd'hui; 2000-2009; angleterre; discipline; europe; hommes*; jeunes adultes; masculinité; périodes historiques; régions géographiques; santé; santé sexuelle; sciences humaines; sexologie; sexualité; thématiques; éducation sexuelle

Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis

L'invention de l'hétérosexualité - Katz, Jonathan (EPEL, 2001)
L'auteur retrace l'histoire du concept d'hétérosexualité. Il analyse les textes d'auteurs comme Freud, Richard von Krafft-Ebing, Michel Foucault, Betty Friedan ou Kate Millet. Il nous montre que la distinction homosexuel/hétérosexuel ne repose pas sur une nature immuable mais constitue une façon récente de classer et de juger la société. [SDM].
Section: 236 pages ; 21 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; analyse de discours; approches et analyses; cours; discipline; discours dominant; europe; france; his4860; histoire; histoire et politique; homosexualité; hétérosexisme; hétérosexualité; identité sexuelle; identités LGBTQIA2+; postmodernisme; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sex1181; sex1183; sexologie; sexualité; shm4000; soc2014; systèmes d'oppressions; thématiques; épistémologie